Vygotsky's Constructivist Approach in the Use of the Boardgame Codenames in Extracurricular Art Education - Bahastika, Ikrar; Sekti, Retnayu Prasetyanti; Trisakti, Trisakti (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
This study aims to describe the application and effectiveness of Codenames board game media that modified in learning fine arts at the extracurricular "Krisna Rupa" at SMAN 1 Situbondo. The method used is descriptive qualitative with the subjects of students and supervising teachers. Data were collected through observation, interviews, and documentation, then analysed using Creswell's approach. The results showed that Codenames was effective in introducing Nusantara fine art terms through word replacement into terms such as batik, wayang, and Asmat sculpture. The game process encouraged students to discuss and understand the cultural context behind the terms used, with the teacher as a facilitator. This application increased students' participation, cooperation, and interest in traditional fine arts. Vygotsky's constructivism approach, particularly in the aspects of ZPD, Scaffolding, and social interaction, was seen to support the learning process. Evaluation through Quizizz showed 84% of students scored above 75, reflecting a good understanding of the material. Thus, the Codenames board game is proven as an innovative, contextual, and fun learning media in improving the understanding of Nusantara fine arts in an extracurricular environment.